Sport and Transcendence through the Body - Dailey, Erik W. (International journal of public theology, 2016)
Where is God in sport? Two important entries have recently been made in the conversation on theology and sport (Lincoln Harvey’s A Brief Theology of Sport and Robert Ellis’ The Games People Play), but neither looks closely at the body itself. To fully understand sport and God’s potential activity in sport, one must look carefully at the body, an obviously key element in all athletic pursuits. Here the two authors’ contributions are compared and assessed and further thought for a more complete theology of sport is offered. Bridging off a theological anthropology of the unified person, without a separable soul or spirit, it is my contention that sport is a medium for refinement of the place—the actual body—where God can meet humankind, and therefore athletic activity is a valuable part of the spiritual life.